Nursing staff facilitate patient participation by championing the patient's perspective: An action research study in spinal cord injury rehabilitation - Randi Steensgaard; Raymond Kolbaek; Sanne Angel (Wiley, 2022)
Abstract Introduction Persons with spinal cord injury have experienced a life‐changing event, and they need to engage in the rehabilitation process to adjust to their current situation and future living conditions. Due to the highly contextual and varying psychological and physical ability to participate from patient to patient during rehabilitation, this is difficult for the injured person and for health professionals to support. Therefore, the aim of the study was to develop and facilitate patient participation by engaging nursing staff and from this engagement in the process, disclose methods to support participation. Methods The processes conducted were based on an action research approach, from problem identification to the development, test and evaluation of four new nursing initiatives. The initiatives were developed by eight nursing staff members who participated actively as co‐researchers in a 2‐year study conducted at a Spinal Cord Injury Centre in Denmark from 2016 to 2018. Data evolved from workshops, transcriptions of meetings and written evaluations and was further analysed using Ricoeur's phenomenological‐hermeneutic approach. Results Action research processes facilitated the development of four communicative initiatives and a shift in the nursing staff's support of the patient. In a collaborative process, the nursing staff acted as participants in the patient's rehabilitation. Awareness of the patient's perspective facilitated a caring, attentive and engaged approach from the nursing staff, which promoted rehabilitation tailored to the individual. Conclusion Patient participation was enhanced when nursing staff actively participated in the development of initiatives and a culture supporting a person‐to‐person approach involving the patient and themselves as equal participants in the collaborative rehabilitation process. Patient or Public Contribution Eight nursing staff members from the rehabilitation centre participated throughout the study as co‐researchers. Patients participated in observations and as informants in interviews during the first phase to identify challenges to patient participation. Patients also participated in testing the nursing initiatives during the action phase (Phase 3). Furthermore, a former patient was a member of the advisory board.